Marketing challenges, trends and opportunities for New Zealand : an inaugural address delivered on 10 July 1991 - Thirkell, Peter, 1953- (Victoria University of Wellington inaugural addresses ;, 1993)
Marketing challenges, trends and opportunities for New Zealand :an inaugural address delivered on 10 July 1991.